Emotional experiences and FLOW in easy bump pistes - Brandauer, T.; Felder, T.; Senner, V. (Science and Skiing IV, 2009)
INTRODUCTION: Skiing resorts have changed. Whereas thirty years ago a number of mogul runs were part of every important resort today the majority of the pistes in European ski resorts are groomed and well prepared. Bump pistes have lost their attraction and are mainly limited to steep terrain where slope preparation cannot be realized. Tremendous improvements concerning equipment (carving skis, snowboards), the preparation of skiing slopes and the absence of mogul runs of variable difficulty are the main reasons for this development. Our study (Felder, 2005) analyses the topic from a motivational and a safety perspective.